Transition and reconstruction in independence : Trinidad and Tobago - a third world challenge - Robinson, A.N.R. (Institute of International Relations St AugustineTT, 1987)
Discusses differences between transition to and in independence. Reviews changes taking place in socialist and capitalist societies, as well as those taken over by a coup, revolution, or where there is a change of government through elections. Discusses transition in Trinidad and Tobago and states what should be its results. Outlines the principles on which reconstruction must be based, its scope, and challenges.